Emil L. Fackenheim : philosopher, theologian, Jew - Portnoff, Sharon; Diamond, James Arthur; Yaffe, Martin D. (Supplements to The journal of Jewish thought and philosophy, 2008)
A tribute to Fackenheim's memory. It covers a spectrum of Fackenheim's work including biographical, philosophical, and theological aspects of his thought.